Evaluation of sustainable consumption behavior according to sociodemographic factors in Indigenous communities - Guido Ayay-Arista; Edwin Gustavo Estrada-Araoz; Judith Annie Bautista-Quispe; Manuel Augusto Mantari-Condemayta; George Jhon Cruz-Visa; Yony Abelardo Quispe-Mamani; Carlos Alberto Canelo-Dávila; José Ricardo Pujaico-Espino; José Alberto Carlos-Ramos (Heritage and Sustainable Development)
Environmental problems represent one of the greatest threats to humanity, which is why environmental sustainability has become an issue of great relevance. In this context, sociodemographic factors are considered to play a fundamental role in the investigation of sustainable consumption behavior, particularly among residents of Indigenous communities. The present study aims to evaluate sustainable consumption behavior in relation to sociodemographic factors in indigenous communities in the Amazon region of Peru. Data were collected through a survey applied to a sample of 319 people selected by stratified probability sampling. The conceptual model and hypotheses were tested by multivariate analysis and structural equation modeling, using the principal component analysis method for factor extraction. As a result, the research revealed a positive connection between pro-environmental factors and sustainable behavioral intention. However, although sustainable behavioral intention was strong, it did not always translate directly into sustainable practices. Significant differences in gender, age, education, income, and occupation were identified as factors influencing sustainable practices. The results highlight the complexity of sociodemographic factors in the adoption of sustainable lifestyles in Indigenous communities. These findings provide a crucial basis for the development of tailored intervention strategies and the formulation of contextualized policies that promote sustainable consumption in these communities.